Bearing Capacity of Annular Foundations on Rock Mass with Heterogeneous Disturbance by Finite Element Limit Analysis - Bo Sung Kim; O-il Kwon; Yong Hyuk Choi; Joon Kyu Lee (Buildings, 2022)
Estimating the performance of foundations on rock mass is essential in designing buildings. Stability assessment of weathered rocks under foundation load is a complicated task if there is an internal opening within the foundation. This study applies finite element limit analysis to evaluate the bearing capacity of annular foundations resting on medium to highly weathered rocks following the modified Hoek–Brown rock mass. Special attention is focused on the effect of rock mass disturbance. The level and heterogeneity of rock mass disturbance are considered as constant or linearly varying disturbance factors with depth, which capture the damage level and zones due to construction and blasting. The results obtained from the analysis compare well with the existing solutions. The numerical results are presented in the familiar form of bearing capacity factors as a function of the dimensionless parameters related to foundation perforation and rock mass properties as well as the foundation-rock interface. The failure patterns of annular foundations are also investigated for a few cases with different levels of disturbance and foundation roughness.